Modification of the existing maximum residue levels for propaquizafop in various crops - European Food Safety Authority (EFSA) (EFSA Journal, 2016)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the evaluating Member State (EMS) Austria, received an application from the company Makhteshim Agan Industries Ltd to modify the existing maximum residue levels (MRL) for the active substance propaquizafop in cauliflowers and various root and oilseed crops. In addition, the EMS Italy received an application from the company ADAMA Quena N.V. to modify the existing MRLs in head cabbages and the group ‘lettuces and salad plants’. Considering that propaquizafop is an ester variant of quizalofop and since two different MRL datasets are proposed for propaquizafop and quizalofop (including quizalofop‐P) under Regulation (EC) No 396/2005, EFSA suggests the two following options: 1) to set specific MRL values for propaquizafop for the crops under consideration; 2) to delete the MRLs for propaquizafop from the EU legislation and to report all MRLs for all quizalofop ester variants in the EU legislation as ‘quizalofop’, considering that the current residue definition reported as ‘quizalofop incl. quizalofop‐P’ would have to be amended to ‘quizalofop and quizalofop esters, including propaquizafop expressed as quizalofop (sum of isomers)’. Sufficient data were submitted to propose specific MRLs for propaquizafop for the crops under consideration, except for the group ‘lettuces and salad plants’ since a sufficient number of trials on open leaf varieties of lettuce has not been provided to support an extrapolation. The deletion of the MRLs for propaquizafop as proposed under option 2 would only request to increase the MRL for mustard seeds from the limit of quantification (LOQ) of 0.05 to 0.06 mg/kg. Based on the risk assessment results, EFSA concludes that the proposed uses of propaquizafop will not result in a consumer exposure exceeding the toxicological reference values and therefore is unlikely to pose a consumer health risk.